Teachers’ actions and children’s interests. Quality becomings in preschool documentation - Katarina Elfström Pettersson (Nordisk Barnehageforskning, 2017)
High quality is considered to be important for children’s development and learning in early childhood education. Swedish preschool teachers are required to systematically develop their practice and support children’s learning, using documentation and taking children’s interests into account. From a posthumanist perspective, preschool documentation, models and templates could be seen as actively producing certain elements of quality.  Reading  documentation from eight Swedish preschool groups diffractively through different texts, such as the national curriculum, supportive texts and research, this article discusses how teachers’ actions and children’s interests are produced as important quality aspects in one of these groups.